A systematic literature review on prototyping with Arduino: Applications, challenges, advantages, and limitations - Kondaveeti, Hari Kishan; Kumaravelu, Nandeesh Kumar; Vanambathina, Sunny Dayal; Mathe, Sudha Ellison; Vappangi, Suseela (Computer science review, 2021)
Arduino, an open-source electronics platform, has become the go-to option for anyone working on interactive hardware and software projects. An Arduino board (such as the Uno) connected to a breadboard with plugins such as inputs, sensors, lights, and displays can be controlled by a code written in the Arduino development environment. How to achieve this is by prototyping with Arduino. Prototyping with Arduino has grown in popularity with the increased use of the Arduino platform. Prototyping with Arduino, however, is not an easy task for nonprogrammers with interest in the field. With increased public interest in the field will come a need for accessible information. This paper presents a methodical literature review intended to intensively analyze and compare existing primary studies on prototyping with Arduino. We found about 130 of such studies, all peer-reviewed and published within the last 15 years, including these years (2015–2020). These studies were tediously and carefully chosen through a three-step process. In this paper, a cautious analysis of selected studies was followed by a clear description of the methods applied. The methods were categorized according to the success rate of the studied prototypes. Results obtained can be used in researches on the best technique to adopt while prototyping with Arduino. They can also be used in electronics researches and by individuals who wish to obtain a guide on prototyping with Arduino despite lacking grounded knowledge of the subject matter.